Emulation of virtual radio environments for realistic end-to-end testing for intelligent traffic systems - Hein, M. A.; Bornkessel, C.; Kotterman, W.; Schneider, C.; Sharma, R. K.; Wollenschläger, F.; Thomä, R. S.; Del Galdo, G.; Landmann, M. (2015 IEEE MTT-S International Conference on Microwaves for Intelligent Mobility, ICMIM 2015, 2015)
We consider two approaches for real-time end-toend over-the-air testing for intelligent traffic systems using virtual radio environments. One approach is based on coherent wavefield synthesis, while the other aims at emulating the essential features of a realistic radio channel in vehicular ad-hoc networks. Due to finite hardware resources, the former is limited to electrically small systems-under-test, while the latter is suited for typical vehicle-to-vehicle scenarios. Three major aspects of the emulation of radio environments in our facilities in Ilmenau, Germany, are described: 1. Emulation hardware, 2. Channel sounding, modeling, and feature extraction, 3. Emulation methods.
CRIS-Team Scopus Importer:2025-11-10
Keywords: channel emulation; intelligent traffic systems; over-the-air; virtual road; virtualradio environment